OPPORTUNITIES OF REMOTE BLOOD PRESSURE MONITORING IN OBSTETRIC PRACTICE: FROM CONTROL TO PREVENTION OF COMPLICATIONS - Agababyan , L.R.; Akhmedova, A.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. Hypertensive disorders affecting 6–8% of pregnant women remain one of the major challenges in modern obstetrics. According to WHO, 20–25% of neonatal deaths are associated with gestational hypertension, especially preeclampsia. Modern telemedicine technologies make it possible to implement remote blood pressure (BP) monitoring as an effective method of control and prevention. Objective: To evaluate the effectiveness of remote BP monitoring in primigravida women for early detection of hypertensive disorders and individualized pregnancy management. Materials and Methods. The study included 178 primigravida women hospitalized at Maternity Hospital No. 2 in Samarkand from 2024 to 2025. Remote BP monitoring was performed using the PBLab telemetric device for three days (8 measurements daily), with automatic data transmission to a central server. Daily mean systolic and diastolic BP, BP variability, nighttime values, and the need for pharmacological correction were assessed. Results. The average systolic BP was 123.5 ± 9.2 mmHg, and diastolic BP — 78.1 ± 6.7 mmHg. Hypertensive episodes were detected in 21.9% of women, and 13.5% required medical treatment. In 38.2% of cases, monitoring data influenced management strategies, while in 17.4%, it helped prevent complications. The most common complications were preeclampsia, fetal growth restriction (FGR), and preterm birth. Conclusion. Remote blood pressure monitoring in pregnant women is an effective tool for early detection of hypertensive episodes, timely initiation of therapy, and prevention of serious complications. This method is especially relevant in regions with limited access to healthcare and aligns with national clinical protocol recommendations.